Whisker Formation On Galvanic Tin Surface Layer - Radanyi A.L.; Sycheva A.; Gacsi Z. (Archives of Metallurgy and Materials, 2015)
The present work reports the effect of substrate composition, thickness of the tin electroplate and its morphology on pressure-induced tin whisker formation. Pure tin deposits of different thickness were obtained on a copper and brass substrates using methane sulfonic industrial bath. The deposits were compressed by a steel bearing ball forming imprint on the surface. The microstructure of tin whiskers obtained at the boundary of each imprint, their length and number were studied using both light and scanning electron microscopy. It was shown that the most intensive formation and growth of whiskers was observed in the first two hours. In general, brass substrate was shown to be more prone to whisker formation than copper independently of the tin coating thickness. The results have been compared with industrial bright tin finish on control unit socket leads and proposals have been made as to modification of the production process in order to minimize the risk of whiskering.